CD14+ monocytes contribute to inflammation in chronic nonbacterial osteomyelitis (CNO) through increased NLRP3 inflammasome expression - Brandt, D (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2018 Elsevier Inc. All rights reserved.